Pour une exploitation didactique de la chanson en classe de langue: l’exemple de Tom du Mali de Romain Didier - Catherine M. Müller (Babylonia)
This paper shows how an in-depth implementation of songs into task-based foreign language learning may allow students to develop cultural and literary awareness while developing the five linguistic competencies. Practical suggestions for teachers are discussed in the printed version; readers may download the corresponding worksheets from the Babylonia website.